2009
DOI: 10.1257/mic.1.1.207
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Winner's Curse: A Laboratory Study

Abstract: The Winner's Curse (WC) is one of the most robust and persistent deviations from theoretical predictions that has been established in experimental economics. We designed and implemented in the laboratory a simplified version of the Acquiring a Company game. Our transformation reduced the game to an individual-choice problem, but one that still retains the key adverse-selection issue that results in the WC. This allows us to isolate the origins of the WC from proposed explanations that have recently been advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(33 citation statements)
references
References 35 publications
2
30
1
Order By: Relevance
“…These results are strikingly complementary to findings from laboratory experiments reported by Charness and Levin (2006). They sequentially strip away all strategic aspects of the environment that leads to the WC.…”
supporting
confidence: 80%
“…These results are strikingly complementary to findings from laboratory experiments reported by Charness and Levin (2006). They sequentially strip away all strategic aspects of the environment that leads to the WC.…”
supporting
confidence: 80%
“…The survey included tests for financial literacy and self‐monitoring. In the five high‐stakes sessions, we also included a Bayesian updating test taken from Charness and Levin (). In four of the five high‐stakes sessions, we asked subjects to assess their session rank on the CRT (see Internet Appendix Section V for the corresponding analysis).…”
Section: Designmentioning
confidence: 99%
“…As discussed in the survey of Kagel and Levin (2002), subsequent laboratory experiments have refined the analysis and have shown that the WC is ‘alive and well’ across student subject pools including super‐experienced' bidders (Kagel and Levin 1999) and is a robust phenomenon in many common value auction forms (see, e.g., Kagel, Battalio, and Walker 1995). Charness and Levin (2005, 4‐5) note, ‘It seems that presently only a few economists doubt the existence of WC‐type of behavior in the lab and more and more are willing to accept that such behavior may indeed exist outside the lab in real markets.’…”
mentioning
confidence: 99%